Optimierung von Gesprächen in der professionellen Telefonie - Pietschmann, Judith (Schriften zur Sprechwissenschaft und Phonetik, 2017)
Telephone service conversations are a central component of social and economic communication practice. They are to a considerable extent pre-planned and standardized. In addition to the desired positive effects (uniformity, efficiency, customer orientation), established call standards lead to unwanted negative effects such as speaking-linguistic stereotypes, over-marking or automated call handling. These and other phenomena are the object of investigation in the research focus on professional telephony at the Martin Luther University Halle-Wittenberg. The author bundles and systematizes the past research work, extended by own investigations and illustrates exemplary approaches, concepts and concrete measures for optimization of conversations in telephone customer service. Judith Pietschmann completed her PhD at the Martin Luther University Halle-Wittenberg in 2017. As a lecturer in the Department of Speech Science and Phonetics, she teaches and researches in the main areas of oral communication in institutional contexts, qualitative and quantitative speech impact research, prosody in interaction and communicative promotion of competence in professional qualification.